Selective Exposure to Berita Harian Online and Utusan Malaysia Online: The Roles of Surveillance Motivation, Website Usability and Website Attractiveness - Zulkafli, Nur Azimah; Omar, Bahiyah; Hashim, Nor Hazlina (2014)
News media allows audiences to be selective in determining both their news sources and type of news stories they read. This study examined factors influencing selective exposure to the online editions of two mainstream Malaysian newspapers, Berita Harian and Utusan Malaysia. Using selective exposure theory as the theoretical lens, this study compared both newspapers in terms of their audiences’ level of surveillance motivation, and how audiences rate the newspapers’ websites with respect to usability and attractiveness. This study used a within-subject experimental research design that exposed 51 subjects to both Berita Harian and Utusan Malaysia online newspapers. The results of the experiment indicate that Berita Harian and Utusan Malaysia online were significantly different in terms of website usability; however, no significant differences were found in terms of surveillance motivation or website attractiveness between the two newspapers. Further analysis indicate that the only significant predictor of selective exposure was website usability. This study highlights the importance of website usability for online newspapers wanting to harness audience selectivity.